2018
DOI: 10.1098/rsos.180797
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of quartz glass in lithium-containing alkaline solutions with or without Ca

Abstract: The exact role of lithium ions (Li+) in controlling alkali–silica reaction is still unclear. Thus, the effects of Li+ on the reaction between reactive silica (quartz glass) and hydroxyl in alkaline solution with or without Ca were investigated by quartz glass powder or slice immersion experiments. When quartz glass was immersed in lithium-containing alkaline solutions, only Li2SiO3 was produced with the absence of Ca, but Li2SiO3 and calcium silicate hydrate (CSH) were formed with the presence of Ca. The quart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…In the presence of calcium, the effect of Li on the dissolutions changes drastically. A significant decrease in SiO 2 dissolution rate in 100 and 1,000 mM NaOH in the presence of both Li and Ca and the formation of a dense C-S-H containing Li were observed (Leemann et al, 2014;Zhou et al, 2018), indicating a destabilization of Li 2 SiO 3 in the presence of calcium. It has been speculated that this Li containing C-S-H layer is responsible for the slowdown of the silica dissolution in the presence of both Li and Ca.…”
Section: Influence On Dissolution Of Silicamentioning
confidence: 97%
See 3 more Smart Citations
“…In the presence of calcium, the effect of Li on the dissolutions changes drastically. A significant decrease in SiO 2 dissolution rate in 100 and 1,000 mM NaOH in the presence of both Li and Ca and the formation of a dense C-S-H containing Li were observed (Leemann et al, 2014;Zhou et al, 2018), indicating a destabilization of Li 2 SiO 3 in the presence of calcium. It has been speculated that this Li containing C-S-H layer is responsible for the slowdown of the silica dissolution in the presence of both Li and Ca.…”
Section: Influence On Dissolution Of Silicamentioning
confidence: 97%
“…Bagheri et al (2021) investigated the effect of Li + under high pH conditions (in 400 mM KOH) and found a clear acceleration of SiO 2 dissolution in the presence of Li + , which might be related to the ability of Li + to form surface complexes on silica. It should be noted that lithium can precipitate in the presence of silica as Li 2 SiO 3 (Zhou et al, 2018;Bagheri et al, 2021), which can lower the measured silicon concentration or mass loss in dissolution experiments (Kurtis and Monteiro, 2003;Tremblay et al, 2010;Leemann et al, 2014;Zhou et al, 2018;Oey et al, 2020;, leading to an apparent decrease in the observed dissolution rate. In the presence of calcium, the effect of Li on the dissolutions changes drastically.…”
Section: Influence On Dissolution Of Silicamentioning
confidence: 99%
See 2 more Smart Citations
“…Through MR experiments, Kim T [21] showed that the most likely mechanism to explain the excellent ability of Li+ ions to inhibit ASR involves the dense physical barrier, which is formed by the reaction products covers delimited areas on the exposed surface of the reactive aggregate. Zhou BF [22] found that quartz glass slices immersed in the alkaline solution with LiNO 3 and Ca(OH) 2 were well protected by a production layer consisting of Li 2 SiO 3 crystals and CSH that densely and firmly covered the surfaces of samples, but seriously corroded in solutions with only LiNO 3 or Ca(OH) 2 .…”
Section: Introductionmentioning
confidence: 99%